Development and Performance Evaluation of a New Conformance Control Agent Gel - Bin Ma; He Wang; Shu Jiang; Mengyu Chen; Lei Zhang (Gels, 2024)
How to effectively plug the multi-scale fractured water channeling has always been the key to achieving efficient water flooding of fractured low-permeability oil reservoirs. In this paper, a new type of supramolecular–polymer composite gel is developed, which is suitable for plugging multi-scale fractured water channeling. The supramolecular–polymer composite gel is composed of a polymer (such as polyacrylamide), cross-linking agent (such as polyethyleneimine), supramolecular gel factor (such as cyclodextrin) and polarity regulator (such as ethyl alcohol). The mass fraction of polyacrylamide, polyethyleneimine, cyclodextrin and ethyl alcohol are 0.15%, 0.2%, 1% and 0.2%, respectively. At the initial state, the viscosity of the composite gelant system is less than 20 mPa·s. It has good injection performance in micro-scale fractures and can enter the deep part of a fractured reservoir. At 40 °C, the composite gelant system can form a gel with a double network structure after gelation. One of the networks is formed by the covalent interaction between polyacrylamide and polyethyleneimine, the other network is formed by the self-assembly of cyclodextrins under the action of the ethyl alcohol. The comprehensive performance of the composite gel is greatly improved. The strength of the composite gel is >5 × 104 mPa·s, and it has good plugging strength in large-scale fractures. The composite gel can be used as a conformance control agent for fractured low-permeability oilfields.